Dynamic monitoring of vegetation coverage in weibei dry plateau based on remote sensing (Bangladesh Journal of Botany, 2023)
Taking Fu County, a typical area of Weibei dry plateau, as the research object, the normalized difference vegetation index ( NDVI ) was calculated by using Landsat 8 OLI remote sensing image. On this basis, the vegetation coverage in the study area was estimated and graded according to the binary pixel model, and the dynamic changes of vegetation coverage in the study area from 2013 to 2017 were quantitatively analyzed. Results showed that the overall NDVI value in the study area increased from 2013 to 2017. The vegetation cover in the study area is dominated by extremely high vegetation cover. The coverage area of low, medium and high vegetation cover decreases, and the coverage area of extremely high and extremely low vegetation cover increases. The coverage area of high vegetation and extremely high vegetation cover accounts for more than 75% of the study area. The study area showed a transfer trend of extremely low vegetation→low vegetation→medium vegetation→high vegetation coverage. The vegetation coverage generally developed to a good trend, but there was also a transfer of high vegetation coverage to medium vegetation coverage. The areas with the greatest changes in the study area are mainly concentrated in the northwest and near the southern Damagou, and the high NDVI area of Ziwuling National Nature Reserve has moved eastward and narrowed. Accuracy assessment indicates that the dynamic monitoring using the fused image time series produces results with relatively high accuracy.Bangladesh J. Bot. 52(2): 479-486, 2023 (June) Special